G29(P) Bringing the curriculum to life. (May 2019) - Okereafor, A; Campbell, O; Ong, A; Jacob, H; Pallawela, J; Jones, V; Davey, N
Abstract : Problem: Lack of knowledge about the new RCPCH curriculum suggested trainees would be unaware and unprepared for the new professional requirements. Aim: All paediatric trainees and consultants in the department to be aware and feel confident to use the new curriculum. Measures: Curriculum awareness and confidence. Change ideas: Focused on identifying learning in everyday experiences and on ways to share these within our team. Small scale tests of change: Face-to-face presentations delivered to trainees and trainers to raise awareness. Neonatal and general paediatric night teams highlight an issue at Monday handover using the 'Learning Point from Our Nights' proforma e.g. unusual cases, difficult resuscitations, parental conflict. Team agreement on learning points mapped to the new curriculum with departmental improvements and further reading. Completed proformas were photographed and shared via WhatsApp and displayed on the curriculum learning boards. Short videos created weekly with the learning points. Focus on mandatory elements of the new curriculum and e-portfolio evidence of the key capabilities. Online learning platform to store and catalogue curriculum learning tools and resources. Sharing with other paediatric departments Results: Baseline data: 0/27 trainees and trainers felt confident to start using the new RCPCH curriculum. Following a series of interventions there was substantial progress in curriculum knowledge: Those responding 'I've heard of it' fell by 18. 'I've read about it and know it' rose by 10. 'I feel confident to start using it in August' increased from zero to nine. Conclusions: Driver: a need to understand and know how to use the new RCPCH Progress curriculum ahead of its launch in August. Change ideas mapped to the new curriculum helped paediatric trainees and consultants increase their curriculum knowledge and confidence. Developing a habit of reflection after night shifts facilitates discussions about decision–making and autonomy, identification of real–time problems and promotes team feedback and cohesion. Disseminating completed templates and bite–sized learning videos via WhatsApp and uploading them to a Trello learning platform enabled the whole team to benefit regardless of shift–pattern. Collaborative learning increased our departments' collective knowledge, encouraged evidence-based learning, improved our professional development and will ultimately enrich our patient care.